Nurses' perceptions about child abuse - Saifan, Ahmad; Alrimawi, Intima A; Bashaireh, Ibrahim (International Journal of Advanced Nursing Studies, 2015)
Background: Despite the efforts to protect children around the world, child abuse and neglect remain serious and global problems. In Palestine, child abuse is hidden under the community culture, does not appear in the Ministry of Health official reports, and little is known about nurses’ perceptions towards this phenomenon.Objectives: To identify nurses’ perceptions about child abuse definition, whether they faced such cases during their work, and how they managed them.Methods: Data were collected using descriptive survey (exploratory) approach. A total of 84 nurses from a major hospital in Ramallah city in Palestine were surveyed.Results: Only 33% of the participants intend to use referral system in co-operation with the Ministry of Social Affairs, child protection organizations, or the police in Palestine to deal with child abuse cases. The most seen abuse case was neglect (79%), followed by psychological abuse (61%), then physical abuse (57%) and the least seen was sexual abuse (27%).Conclusion: Most of the participants do not know how to deal with child abuse effectively. This research provides baseline information for understanding nurses’ practice in the ground, and it helps in presenting the appropriate conditions that enable nurses to fully practice their role toward such cases.